Communicating to and engaging with the public in regulatory science. (8th July 2019) - Smith, Anthony; Parrino, Lucia; Vrbos, Domagoj; Nicolini, Giulia; Bucchi, Massimiano; Carr, Melanie; Chen, Junshi; Dendler, Leonie; Krishnaswamy, Kannan; Lecchini, Davide; Löfstedt, Ragnar; Patel, Michelle; et al.
Abstract: This paper presents selected highlights from the 'Engaging with society' session of EFSA's third Scientific Conference 'Science, Food and Society' (Parma, Italy, 18–21 September 2018). The social dimension for scientific advisory bodies largely concerns science communication and public engagement. The political, economic and technological transformation of contemporary societies is challenging conventional structures and approaches in these areas. The disintermediation of communication and the proliferation of misinformation, it is argued, herald the onset of the post‐truth society. A better understanding of the way individuals consume information today has led to the development of tools to guide mediators such as journalists and communication specialists in countering these trends. Public engagement can reinforce confidence in regulatory bodies and potentially contribute to the quality of the scientific process. Scientific advisory bodies in Europe have created strategies and mechanisms to engage the public that are designed to increase transparency and representativeness. To be effective, several engagement mechanisms are needed, although factors such as resource constraints, institutional culture and public/stakeholder attitudes may limit their development. In conclusion, a more vigorous role for social research is needed to place scientific risk assessment within broader socio‐economic and political contexts. Social science expertise can help to define more impactful public information strategies and to explore the potential opportunities that engaged stakeholders and citizens can make to sustain and strengthen regulatory science.